The Use of Arabic Calligraphy Items in Decorative Designs for Islamic Fabrics and Costumes: الهام طاهر حسين (Al-Academy, 2019)
The Arabic calligraphy, in the early days of Islam, was used for the purpose of decorating the walls of mosques from inside and outside. Hence, this decorative art must be actively involved in enriching the designs of Islamic fabrics and costumes because it has a highly qualified and aesthetically pleasing look and expresses the originality of the Arab spirit. The research is divided into two section: the first section included the following topics: First "A historical overview of the art of decoration in Islamic Arab thought". Second "linear formations of decorative designs, and the subject of intellectual aesthetic taste of the art of decorating. This section tackles two subsections: first "the beauty of thought between the function and abstraction", second " The calligraphic decorative designs and their relationship to the human body". The research procedures included presenting a design proposal for the latest robes containing vocabulary chosen from the aesthetics of the Arabic and Islamic Calligraphy. Then, the most important results were included as follows: The decorative diversity is adding vitality and aesthetics in a thoughtful way, especially when accompanied by the formal unit of the costume that it produces an innovative design. The research ends with a list of sources and references